Steroid epidural injections in treatment of radicular syndrome caused by degenerative-dystrophic diseases of the spine - Kvasnitskyi, Mykola; Kvasnitskyi, Oleksandr (Ukrainian Neurosurgical Journal, 2014)
Introduction. The high frequency of degenerative-dystrophic diseases of the shine has necessitated introduction into clinical practice of effective method for steroids epidural injection for the treatment of radicular syndrome caused by degenerative spine. The purpose. To improve efficacy of treatment of patients with radicular syndrome caused by degenerative diseases of the spine, through scientifically based definition of indications for steroids epidural injection. Materials and methods. Early and remote results of 76 patients treatment with radicular syndrome (study group), aged from 38 to 82, using only epidural injections of steroids were analyzed. In the control group there were 30 patients, aged 42 to 79 years, they have been treated conservatively. Results. Significant difference of early and remote results of treatment in two groups of patients was found according to Oswestry Disability Index and Visual Analog Pain Scale. Conclusions. The high efficacy of epidural injections of steroids was shown in treatment of radicular syndrome caused by degenerative-dystrophic diseases of the spine. Epidural injections of steroids are indicated at intervertebral disks herniation (diameter up to 9 mm), spine canal stenosis, spondylolistheses, spondylarthroses that cause radicular syndrome.